2007
DOI: 10.1258/000456307780945778
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical assessment of insulin resistance

Abstract: Addresses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 107 publications
2
134
0
1
Order By: Relevance
“…However, several studies have demonstrated that results obtained using HOMA-IR correlate well with results using the euglycemic, hyperinsulinemic clamp technique. 36,55 Slight reductions in creatinine clearance were seen from baseline to week 12 in both treatment arms of this study; however, these reductions were no longer apparent after 48 weeks of treatment. A previous study suggested an association between the use of ATV, TDF, or indinavir and creatinine clearance, as indicated by a persistent reduction in glomerular filtration rate over time.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, several studies have demonstrated that results obtained using HOMA-IR correlate well with results using the euglycemic, hyperinsulinemic clamp technique. 36,55 Slight reductions in creatinine clearance were seen from baseline to week 12 in both treatment arms of this study; however, these reductions were no longer apparent after 48 weeks of treatment. A previous study suggested an association between the use of ATV, TDF, or indinavir and creatinine clearance, as indicated by a persistent reduction in glomerular filtration rate over time.…”
Section: Discussionmentioning
confidence: 74%
“…36 The lower limits of quantification (laboratory variability; normal reference range) for the biomarker assays are as follows: IL-1 beta, 0.125 pg/ml (6.7%; < 0.201 pg/ml); IL-6, 0.2 pg/ml (4.3%; < 11.83 pg/ml); TNF RII, 1 pg/ml (2.6%-4.8%; 1003-3170 pg/ ml); hs-CRP, 0.15 mg/liter ( < 2%; < 5.00 mg/liter); fibrinogen, 42 mg/dl ( < 4%; 211-372 mg/dl); and d-dimer, 109 ng/ml ( < 4%; < 201 ng/ml; ICON Central Laboratories Inc., Farmingdale, NY). For the determination of LPS concentration, the QCL-1000 assay (Lonza Biologics Inc., Walkersville, MD), with a sensitivity range of 0.1-1.0 endotoxin units/ml (1 endotoxin unit = 100 pg), and low intraassay variability, was used.…”
Section: Study Evaluationsmentioning
confidence: 99%
“…Different methods to assess insulin resistance are currently available and they include fasting measurements of insulin and glucose, the OGTT, the insulin tolerance test, the hyperinsulinemic euglycemic clamp and the frequently sampled i.v. glucose tolerance test (FSIVGTT) (62).…”
Section: Assessing Insulin Resistancementioning
confidence: 99%
“…The two most common tests to measure insulin sensitivity are the hyperinsulinemic euglycemic clamp and the FSIVGTT utilizing the minimal model (62). These methods are accurate and, when labelled glucose tracers are used, they also allow differentiation between hepatic and muscular insulin resistance (62).…”
Section: Assessing Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation